The Relationship Between AST/ALT Ratio and Metabolic Syndrome in Han Young Adults - AST/ALT Ratio and Metabolic Syndrome - Lu, Qiang; Liu, Xiaoli; Liu, Shuhua; Xie, Changshun; Liu, Yali; Ma, Chunming (IntechOpen, 2012)
None